Nanofabrication of (Cr2O3)x(NiO)1-xand the impact of precursor concentrations on nanoparticles conduct - Al-Hada N.M.; Al-Ghaili A.M.; Kasim H.; Saleh M.A.; Baqiah H.; Liu J.; Wang J. (Elsevier Editora Ltda, 2023)
Calcination; Chromium compounds; Energy gap; Fourier transform infrared spectroscopy; High resolution transmission electron microscopy; Nanoparticles; Nickel oxide; Particle size; Particle size analysis; Photoluminescence; Polyvinyl alcohols; Structural properties; Synthesis (chemical); X ray diffraction; X ray photoelectron spectroscopy; (cr2O3)x(NiO)1-xnanoparticle; Calcination technique; Fourier transform infra reds; Optical-; Precursor concentration; Property; Transform infrared spectroscopy; Transmission electron; X-values; Optical properties